\(x+y+z=\frac{x}{y+z-3}=\frac{y}{x+z-4}=\frac{z}{x+y+7}\)
Với \(x+y+z=0\) dễ dàng có được \(x=y=z=0\)
Với \(x+y+z\ne0\) áp dụng tính chất dãy tỉ số bằng nhau ta có:
\(\frac{x}{y+z-3}=\frac{y}{x+z-4}=\frac{z}{x+y+7}=\frac{x+y+z}{2\left(x+y+z\right)}=\frac{1}{2}\)
\(\Rightarrow x+y+z=\frac{1}{2}\Leftrightarrow\hept{\begin{cases}y+z=\frac{1}{2}-x\\x+z=\frac{1}{2}-y\\x+y=\frac{1}{2}-z\end{cases}}\)
Suy ra: \(\frac{x}{\frac{1}{2}-x-3}=\frac{y}{\frac{1}{2}-y-4}=\frac{z}{\frac{1}{2}-z+7}=\frac{1}{2}\)
Dễ r:v